2013
DOI: 10.1155/2013/169356
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Ultrasensitive Cardiac Troponin I Assay in Intermediate- and High-Risk Surgery Patients

Abstract: Background. Cardiac troponin levels have been reported to add value in the detection of cardiovascular complications in noncardiac surgery. A sensitive cardiac troponin I (cTnI) assay could provide more accurate prognostic information. Methods. This study prospectively enrolled 142 patients with at least one Revised Cardiac Risk Index risk factor who underwent noncardiac surgery. cTnI levels were measured postoperatively. Short-term cardiac outcome predictors were evaluated. Results. cTnI elevation was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The combination of these three lncRNAs enhanced the specificity and sensitivity to diagnose CAD. For years, NT‐proBNP, CKMB, MYO or HsTnT have been proposed to be the diagnostic criteria for CAD . Logistic regression analysis indicated that these lncRNAs are cooperative predictive biomarkers for CAD: APOA1‐AS was associated with NT‐proBNP, CKMB, MYO and HsTnT; and HIF1A‐AS2 was associated with NT‐proBNP and NT‐proBNP.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these three lncRNAs enhanced the specificity and sensitivity to diagnose CAD. For years, NT‐proBNP, CKMB, MYO or HsTnT have been proposed to be the diagnostic criteria for CAD . Logistic regression analysis indicated that these lncRNAs are cooperative predictive biomarkers for CAD: APOA1‐AS was associated with NT‐proBNP, CKMB, MYO and HsTnT; and HIF1A‐AS2 was associated with NT‐proBNP and NT‐proBNP.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that elevated PreOp hs-cTnI concentrations in patients with cardiovascular risk factors are independently associated to the development of MACE and death. Borges et al reported that a peak level of PostOp hs-cTnI > 40 pg/ml was associated to decreased survival and decreased event-free survival by day 30 14 . Likewise, a greater increase in the PreOp and PostOp Δ hs-cTn is associated with a greater incidence of the analyzed outcomes 5,[15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies that have investigated the role of perioperative measurement of cTns evaluated patients undergoing noncardiac surgery, rather than solely on TJA, and were assessing for myocardial injury [23,26,28] and infarction [21][22][23][24][25][26][27] (see Table 1). These studies have a great deal of heterogeneity in the specific assays and timing of troponin measurement, as well as specific populations within the larger grouping of noncardiac surgery.…”
Section: Troponins As a Marker Of Cardiovascular Risk In Noncardiac Smentioning
confidence: 99%
“…Other studies have found increased levels of cTnI or cTnT (including hs-cTnT), drawn preoperation and or for any of the first three mornings postoperation [21,[23][24]26,28,32], or for at least two consecutive days postoperation [22,25,34] were helpful in identifying risk for postoperative cardiac complications for up to 1 month [23,[25][26][28][29]], 1 year [32] and up to 5 years [21,24,34] following surgery. In addition to increased postoperative morbidity, both cTnI and cTnT or hs-cTnT have been associated with identifying increased risk of mortality.…”
Section: Troponins As a Marker Of Cardiovascular Risk In Noncardiac Smentioning
confidence: 99%